A New Pressure Regularity Criterion of the Three-Dimensional Micropolar Fluid Equations - Junbai Ren (Journal of Applied Mathematics)
This paper concerns the regularity criterion of the weak solutions to the three-dimensional (3D) micropolar fluid equations in terms of the pressure. It is proved that if one of the partial derivatives of pressure satisfies ∂3π∈Lp(0,T;Lq(R3)) with 2/p+3/q≤2,3<q<∞,1<p<∞, then the weak solution of the micropolar fluid equations becomes regular on (0,T].